Effects of Red Pepper Pomace Protein and Oil on the Properties of Starch-Based Edible Films - Akinci, Zeynep Kader; Karaman, Halil; Yildirim-Yalcin, Meral; Olcay, Hatice Sena; Inan, Mehmet; Toker, Omer Said (SPRINGER, 2024)
PurposeAs the issue of sustainability gains importance in recent days, efforts to reduce or eliminate waste problems are gaining importance. The use of various industrial by-products is being investigated to produce edible packaging materials. In this study, red pepper pomace oil and protein were extracted and incorporated into corn starch film and their effects on the film properties were analyzed.MethodProtein isolate was added to the films as 10-30% of the starch mass and oil as 15% of the solid mass of the film containing 10% protein isolate. The edible composite films characterized by physical, barrier, mechanical, antioxidant and antimicrobial properties and FTIR spectroscopy.ResultsPomace oil addition increased the thickness. While pomace oil decreased water solubility, protein isolate increased it. Protein isolate and pomace oil did not alter swelling and water vapor permeability. The protein isolate decreased the L* value and the pomace oil decreased the a* value. Both protein isolate and pomace oil increased yellowness in the films. A low amount (10%) of protein isolates increased the transparency of films. The combined use of protein isolate and pomace oil decreased the elongation at break and increased the tensile strength of the films. Antimicrobial effect against Escherichia coli and antioxidant activity of oil containing film were observed.ConclusionThe results suggest that valuable components can be obtained from red pepper pomace, and these components can be added to modify the characteristics of maize starch edible films.
Keywords: Food Waste; Red Pepper Pomace; Starch film; Protein Isolate; WATER-VAPOR PERMEABILITY; MECHANICAL-PROPERTIES; BARRIER PROPERTIES; PHYSICOCHEMICAL PROPERTIES; ANTIMICROBIAL PROPERTIES; PHYSICAL-PROPERTIES; CASSAVA STARCH; COMPOSITE FILM; DIETARY FIBER; ISOLATE; Environmental Sciences & Ecology